A Development of a Critical Thinking Board Learning Tool in Social Studies Lessons to Improve Student Learning Outcomes at State Junior High School 18 Surabaya - Ainur Rosyidah (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to develop a Critical Thinking Board learning resource to improve students’ learning outcomesin the Social Studies subject, specifically on the topic of social change caused by technology.The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The research subjects were 15 Year 9 students from Class IX F at State Junior High School 18 Surabaya. Data were collected through validation by media and subject matter experts, astudent response questionnaire, and pre-test–post-test assessments. Data analysis was conducted using the feasibility percentage and the N-Gain test. The results of the study indicate that the teaching aid received 88% validation from media experts and 89% validation from subject matter experts, both of which fall into the ‘highly feasible’ category. Student response to the media reached 84.62%, falling into the ‘very good’ category. The results of the effectiveness test showed an improvement in student learning outcomes with an N-Gain value of 0.07. Based on these findings, the Critical Thinking Board learning medium is deemed suitable, practical, and effective for use in Social Studies lessons on social change caused by technology.